Endoplasmic reticulum stress in the development of multiple myeloma and drug resistance. Issue 1 (29th January 2018) - Nikesitch, Nicholas; Lee, James M; Ling, Silvia; Roberts, Tara Laurine
Abstract: Multiple myeloma (MM) is a haematological malignancy of mature antibody‐secreting plasma cells. Currently, MM is incurable, but advances in drug treatments have increased patient lifespan. One of the characteristics of MM is the excessive production of monoclonal immunoglobulin (also referred to as paraprotein). This high level of protein production induces endoplasmic reticulum (ER) stress, and proteasomal degradation of the paraprotein is required to avoid ER stress‐induced cell death. Consequently, proteasomal inhibitors such as bortezomib have been particularly effective therapies. Unfortunately development of resistance to bortezomib is common. In this review, we address how control of endoplasmic reticulum stress is important in the development of MM and how the unfolded protein response and its associated stress response pathways are involved in the development of bortezomib resistance. Abstract : The majority of multiple myeloma (MM) patients produce large amounts of immunoglobulin fragments (also called paraprotein). This excessive level of protein secretion increases endoplasmic reticulum (ER) stress, resulting in activation of compensatory pathways including the unfolded protein response and increased protein degradation. Proteasome inhibitors (PIs) have been effective in MM treatment as they result in overwhelming ER stress and the resulting cell death; however, resistance is common. Current and future research focuses on understanding the complex pathways activated by and regulating ER stress, with the aim of improving treatment for MM patients especially those resistant to PIs.